(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The value of Gene Xpert MTB/RIF bronchial lavage fluid in diagnosing pulmonary tuberculosis. Method: Descriptive, cross-sectional. The research was conducted on 120 patients suspected of pulmonary tuberculosis with negative sputum AFB, who admitted to the Respiratory Department of Thong Nhat hospital from July 2022 to August 2023. Results: Pulmonary tuberculosis patients with negative AFB sputum: 67.9% male and 32.1% female. Mean age was 57.8 ± 20.1 years and BMI 21.4 ± 1.8 kg/m2. Comorbidities included: hypertension 41.1%; type 2 diabetes 30.4%; chronic lung disease 5.4%. History of smoking 16.1%. 48.2% of patients had lesions in more than 1 location; right lungs 46.4%; lelf lungs 28.6%; upper lobe 51.8%; lower lobe 17.8%. Infiltrative lesions 64.3%; consolidation 21.4%; pleural effusion 10.7%; 8.9% cavernous and 5.4% nodular. Gene Xpert MTB/RIF bronchial lavage fluid had tuberculosis bacteria in 40.8% cases; MGIT MTB (+) bronchial lavage fluid 46.7%. Sensitivity of Gene Xpert MTB/RIF compared to MGIT bronchial lavage (Se) 85.7%; specificity (Sp) 98.4%; positive predictive value (PPV) 97.9%; negative predictive value (NPV) 88.7%. Rifampicin resistance rate is 4.1%. Conclusion: Pulmonary tuberculosis patients with negative AFB sputum have diverse clinical and radiological characteristics. Gene Xpert MTB/RIF bronchial lavage fluid has high sensitivity and specificity in diagnosing AFB-negative pulmonary tuberculosis, and rifampicin resistance rate is 4.1%.